Estudio de factibilidad para la creacion de una microempresa manufacturera de zapatillas, de tagua y cuero, canton Quevedo, año 2013 - Santos Bayas, Karen Adriana (2013)
In this draft feasibility study for the creation of a manufacturing microenterprise leather slippers and tagua, is drawn to publicize all areas managed in a micro-enterprise, development, processing and finishing of it , not to mention the human part that is definitely as important as any other. . The project objectives were l as follows: Designing a questionnaire, which will allow us to meet the unmet demand, sales levels , competitive pricing and strategies to be used for project feasibility . Identify the design innovation in the production of shoes, affects the level of acceptance of citizenship and its effect on the growth of the commercial sector Quevedo Canton Analyze costs, production costs, environmental impact and see -ing involved in the project To determine the return on investment in the project. Strategies will run advertising campaigns, enabling customers know the prod-ucts offered by our factory. Perform motivational talks and human relations staff. In addition to meeting the demands of our consumers, this project aims to re-vive the economy through consumption of raw materials such as tagua and leather, in the manufacture of shoes and selling them. This expanded the base input suppliers are offering job and trade will have a new product aimed at the population.